A Scoping Review of International Experiences by U.S. Extension Professionals: Lessons and Opportunities - Benjamin B. Grove; Sarah A. Bush; Jeremy Elliott-Engel (Journal of International Agricultural and Extension Education, 2024)
The U.S. Cooperative Extension System (CES) faculty and administrators have contemplated internationalization for decades. A proposed way to support internationalization of CES is international extension experiences. This scoping review assessed the literature from 1980-2020 on direct international extension experiences of Extension professionals. Nineteen articles were included in the study after careful screening. We coded for the benefits that resulted from each article: (a) global/international perspectives, (b) personal belief in the value of international experiences, (c) learning/knowledge gains/skills building, (d) appreciation for diversity, (e) increased perceived value of Extension, (f) self-esteem/reinvigoration, and (g) benefits to domestic clientele. Emergent themes were found from coding the results of included papers, including: (h) networking, (i) opening markets, (j) improved policy, (k) conservation of resources, (l) personal openness to change, (m) problem solving; and, (n) technology. Gaps remain in empirical results that explain the benefits of direct international experiences by U.S. Extension professionals, contributions of such experiences to Extension internationalization, and programmatic elements required for program effectiveness.
Keywords: internationalization; globalization; international Extension experiences; land-grant university engagement